2008
DOI: 10.1080/07408170701761938
|View full text |Cite
|
Sign up to set email alerts
|

Variance reduction techniques: Experimental comparison and analysis for single systems

Abstract: We provide a thorough analysis of the effectiveness of different Variance Reduction Techniques (VRTs). We consider both stand-alone and combined applications of two input techniques, Antithetic Variates (AV) and Latin Hypercube Sampling (LHS), and two output techniques, Control Variates (CV) and Poststratified Sampling (PS). Previous research in the area mainly focuses on asymptotic variance reduction. In this experimental study, we measure the performance of VRTs under finite simulation run lengths and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…When applying the stratified sampling technique, we must know the exact distribution of the stratification variable, which is usually assumed to be normally distributed, at least asymptotically, in the related literature. For the determination of the boundaries between the strata, the experimental results from existing literature often reveal that Sethi's stratification scheme is better than the equal‐probability scheme (eg, Sabuncuoglu et al, ). Therefore, in the current experiments we use Sethi's optimal stratification scheme for a normal random variable under proportional allocation to classify each of the replicated observations {Yi,Ci,Di} into the appropriate stratum.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…When applying the stratified sampling technique, we must know the exact distribution of the stratification variable, which is usually assumed to be normally distributed, at least asymptotically, in the related literature. For the determination of the boundaries between the strata, the experimental results from existing literature often reveal that Sethi's stratification scheme is better than the equal‐probability scheme (eg, Sabuncuoglu et al, ). Therefore, in the current experiments we use Sethi's optimal stratification scheme for a normal random variable under proportional allocation to classify each of the replicated observations {Yi,Ci,Di} into the appropriate stratum.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Therefore, in the current experiments we use Sethi's optimal stratification scheme for a normal random variable under proportional allocation to classify each of the replicated observations {Yi,Ci,Di} into the appropriate stratum. In the literature on PS technique, L is often specified in the range of 2L6, where it is experimentally found that the marginal efficiency gain may not be significant when using more than 4 strata (see Chapter 5 of Cochran (), Sabuncuoglu et al (), and Wilson and Pritsker ()). In the following experimental study, we use L=2 and 4.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the case of a queuing system with a single server, Page [27] and Mitchell [28] applied AV to the generation of exponentially distributed customer inter-arrival and service times, noting reductions of up to 41% in the standard error of the estimated average customer waiting time when compared to simulation by SRS. Sabuncuoglu et al [29] experimented with AV and LHS in turn for the same queuing system, observing reductions of up to 16% in the standard error of the estimator of the total time spent in the system relative to SRS. Ross and Lin [30] advocate stratification of the number of customer arrivals in queuing systems as opposed to inter-arrival times and obtained a reduction in the standard deviation of the average customer waiting time of 29%.…”
Section: Queuing Systemsmentioning
confidence: 99%